2015
DOI: 10.29252/jnkums.6.4.925
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between food habits with body mass index (BMI) and fat distribution (WHR) in high school girls in Bojnurd

Abstract: Background & Objectives: Obesity is the most important nutrition-health problem of adolescents in developed countries, and the role of dietary habits and associated factors in nutritional disease is undeniable. Furthermore, weight gain especially in adolescence is associated with negative attitudes to own their. This study examined the relationship between food habits with body mass index and fat distribution in high school girls in Bojnurd. Materials and Methods: This cross-sectional study was conducted on 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of a previous study conducted on candidate patients for orthopedic surgery showed that using the NSM reduced the anxiety level in patients waiting for surgery (Nasiry Zarrin Ghabaee et al, 2015). Moreover, the finding of another study indicated that applying this model may reduce the level of stressors in patients scheduled for CABG surgery.…”
Section: Discussionmentioning
confidence: 97%
“…The results of a previous study conducted on candidate patients for orthopedic surgery showed that using the NSM reduced the anxiety level in patients waiting for surgery (Nasiry Zarrin Ghabaee et al, 2015). Moreover, the finding of another study indicated that applying this model may reduce the level of stressors in patients scheduled for CABG surgery.…”
Section: Discussionmentioning
confidence: 97%
“…This finding was in line with the findings of the studies conducted by Safarjani et al .,[ 22 ] who assessed the nutritional knowledge and anthropometric status as well as findings of the study conducted by Nasiri Zarrin Ghabaee et al . [ 23 ] on female high school students in Bojnurd in 2012. In addition, no relationship was found between BMI and nutritional knowledge.…”
Section: Discussionmentioning
confidence: 99%